White women, Aboriginal missions and Australian settler governments: maternal contradictions - Cruickshank, Joanna (Studies in Christian mission, 2019)
Mission and marriage in early Colonial contexts -- Mothers and daughters in Victoria -- Wives, widows and sisters in far North Queensland -- Single white women and faith missions -- Beyond protection in Southeastern Australia -- Teachers and nurses in the north.